Salvatore Schiavo-Campo y Hans W. Singer. Perspectives of economic development. Boston, [Mass.] : Houghton Mifflin Company, 1970. 351 p. - Appendini, Kirsten A. de (Estudios Demográficos y Urbanos, 1972)
SALVATORE SCHIAVO-CAMPO y HANS W. SINGER, Perspectives of Economic Development, Boston, Houghton Mifflin Company, 1970.